POLITICAL STRATEGY OF WOMEN’S LEGISLATIVE MEMBERS OF THE REPUBLIC OF INDONESIA FROM NATIONAL MANDATE PARTY (PAN) AND NATIONAL AWAKENING PARTY (PKB) IN THE 2019 GENERAL ELECTIONS - Suryani Suryani; Ana Sabhana Azmy (JWP (Jurnal Wacana Politik), 2023)
Women have an important role in politics, where their representation becomes a role model for other women. PAN and PKB are the two parties that won quite a large number of votes in the 2019 elections. However, the percentage of elected women legislators from these two parties does not represent the fulfillment of the 30% quota. This paper analyzes the strategy for selecting women members of PAN and PKB in the 2019 elections, using qualitative research methods. Through interviews and literature searches in the form of books and journals as well as other supporting references, this research yielded several important results. The results of this study indicate that there is a use of resources and funding by women legislators as part of the campaign. As for the differences in the strategy for electing women legislators between the two parties, that PAN women are more on the use of personal social networks and not through ‘Aisyiyah and PUAN. This is different from the PKB, in which elected women legislators use social and political capital from their involvement in Fatayat NU and women of the nation. The supporting factors for the election of both were due to the socio-political capital possessed and the figure of a female legislature member. While the inhibiting factors come from the patriarchal perspective of society as well as competition with male and female legislative candidates, both from the same party and not.